True love cowboy - Ryan, Jennifer, 1973- (Ryan, Jennifer, 1973- McGrath., 2021)
"Jon Crawford has returned to Montana, determined to take over his father's ranch and raise his daughter in Big Sky Country, leaving the big-city life behind once and for all. He doesn't have time to fall in love, but he doesn't count on Trinity McGrath, who arouses his protective instincts even as she tries to push him away. Life hasn't always been easy for Trinity, but now she has everything she needs--her family, friends, and a safe and secure life. With a business to build, Trinity doesn't have time for romance until Jon comes barging into her life and all her intentions are turned upside down! Still, an attraction like theirs is too powerful to deny, and sometimes true love comes along when you least expect it. But when someone from Jon's past comes back with a vengeance, Trinity and Jon will have to do everything they can to save themselves and their new love"--